Perbandingan Matlamat Pendidikan Dalam Situasi Pendidikan Dualistik: Nukilan D·aripada Data Kajilidikan - Zon, Khadijah (Penerbit Universiti Sains Malaysia, 1989)
Using the term 'educational goals', the article focuses on the situation (among the Malays of Peninsula Malaysia) wherein two educational 'systems' have emerged, involving the Islamic religious schools on the one hand, and the national school system on the other. The explicit educational goals of the two systems are drawn from the writer's own case study (1985 - 1987), and the 'divergences' are indicated by comparing all the f.ive educational goals of the two systems. The article concludes that the divergences in educational goals could lead to irretrievable differences in value orientations; the problem thus needs to be addressed systematically and professionally